Pengaruh Likuiditas, Profitabilitas, dan Leverage terhadap Kebijakan Dividen pada Perusahaan LQ45 - Kaswanti, Ferna; Mayliza, Riri (ARZUSIN, 2025)
This research is motivated by the inconsistent findings of previous studies regarding the factors that influence dividend policy, particularly in companies listed in the LQ45 index on the Indonesia Stock Exchange. The purpose of this study is to examine the effect of liquidity, profitability, and leverage on dividend policy in LQ45 companies during the 2019–2023 period. This study employs a quantitative approach using purposive sampling, resulting in 24 companies selected as samples with a total of 108 observations. The data were obtained from the companies’ financial statements, and the variables used include the current ratio, return on equity, debt to asset ratio, and debt to equity ratio. Data analysis was conducted using panel data regression with the help of the Eviews 12 software. The results indicate that liquidity has no significant effect on dividend policy. Meanwhile, profitability (Return on Equity) and leverage (Debt to Asset Ratio and Debt to Equity Ratio) have a positive and significant effect on dividend policy. These findings suggest that companies with high profitability and a sound capital structure tend to be more capable of distributing dividends to shareholders. This study has implications for investors in evaluating financial indicators before making investment decisions and serves as a reference for future research related to dividend policy in the Indonesian capital market.